SYNERGISTIC EFFECTS OF DIETARY POLYPHENOLS AND PHYSICAL ACTIVITY ON IRRITABLE BOWEL SYNDROME: A REVIEW OF GUT BARRIER FUNCTION, INFLAMMATION AND MICROBIOTA MODULATION - Torbacka, Emilia; Siedlecki , Rafał; Góral, Marta; Fidorowicz , Dominik; Sagan, Daniel; Sergiel, Katarzyna Helena; Skuza, Aleksandra Irena; Downar-Zapolska, Magda; Mikłaszewicz, Agnieszka; Bednarczuk, Katarzyna (International Journal of Innovative Technologies in Social Science, 2026)
Irritable bowel syndrome (IBS) is a common disorder of gut/brain interaction characterised by abdominal pain and altered bowel habits with a substantial burden on quality of life. Increasing evidence implicates disrupted gut barrier function, low‑grade mucosal inflammation and microbiota shifts as key pathophysiological mechanisms. Dietary polyphenols possess anti inflammatory, antioxidant and prebiotic activity. A growing number of randomised controlled trials demonstrate that polyphenol based nutraceuticals improve IBS symptoms and quality of life. Similarly, increasing physical activity appears to reduce global IBS symptoms, even though the certainty of the evidence is very low. However, mechanistic validation remains limited. Most trials prioritise patient reported outcomes over integrated multi domain biomarker phenotyping and no IBS study has directly tested whether combined polyphenol and physical activity interventions produce synergistic effects. This review integrates evidence on polyphenols and physical activity in IBS, focusing on gut barrier function, inflammation and microbiota modulation. The findings show that inflammatory modulation (CRP, IL‑6, TNF‑α, GM‑CSF) is the most consistently supported mechanistic domain, while barrier proxies (zonulin, I‑FABP) often remain unchanged despite clinical benefit. Convergent pathways from mechanistic exercise studies and animal models suggest biological plausibility for synergy, but evidence based testing in IBS is lacking. To determine whether combining lifestyle strategies produces synergistic, clinically meaningful benefits in IBS, future factorial trials must include interaction testing. They should also integrate coordinated measurements of clinical, barrier, inflammatory and microbiome endpoints.